Degree of hydrolysis and antigenicity of buffalo alpha S1 casein and its hydrolysates in children with cow milk allergy. Issue 1 (2nd January 2016) - Ahmad, Nazir; Imran, Muhammad; Khan, Muhammad Kamran; Nisa, Mahr un
Abstract : Antigenicity of buffalo alpha S1 ( α -S1) casein and its hydrolysis by gastrointestinal enzymes were carried out in this study. α -S1 casein was purified by anion exchange chromatography and hydrolyzed for 150 min. Indirect Enzyme-linked immunosorbent assays were performed using sera of groups of patients allergic to cow milk and healthy group of subjects non-allergic to cow milk. The patients allergic to cow milk showed significant response to α -S1 casein, which reduced with higher degree of hydrolysis. Maximum reduction of antigenicity was observed for trypsin at 85%. Similarly, α - chymotrypsin at pH 7.8, pepsin at pH 2.2 and pH 5.5 reduced the antigenicity to 63%, 60% and 38%, respectively. The enzymatic hydrolysis can reduce the antigenicity of buffalo α -S1 casein in patients allergic to cow milk. However, a complete inhibition of immunogenic reaction requires supplementary treatment beyond gastrointestinal enzymes.